Acupressure for smoking cessation - a pilot study - Moody Russell C; White Adrian R; Campbell John L (BMC, 2007)
Abstract Background Tobacco smoking is a serious risk to health: several therapies are available to assist those who wish to stop. Smokers who approach publicly funded stop-smoking clinics in the UK are currently offered nicotine replacement therapy (NRT) or bupropion, and group behaviour therapy, for which there is evidence of effectiveness. Acupuncture and acupressure are also used to help smokers, though a systematic review of the evidence of their effectiveness was inconclusive. The aim of this pilot project was to determine the feasibility of a study to test acupressure as an adjunct to one anti-smoking treatment currently offered, and to inform the design of the study. Methods An open randomised controlled pilot study was conducted within the six week group programme offered by the Smoking Advice Service in Plymouth, UK. All participants received the usual treatment with NRT and group behavioural therapy, and were randomised into three groups: group A with two auricular acupressure beads, group B with one bead, and group C with no additional therapy. Participants were taught to press the beads when they experienced cravings. Beads were worn in one ear for four weeks, being replaced as necessary. The main outcome measures assessed in the pilot were success at quitting (expired CO ≤ 9 ppm), the dose of NRT used, and the rating of withdrawal symptoms using the Mood and Symptoms Scale. Results From 49 smokers attending four clinics, 24 volunteered to participate, 19 attended at least once after quitting, and seven remained to the final week. Participants who dropped out reported significantly fewer previous quit attempts, but no other significant differences. Participants reported stimulating the beads as expected during the initial days after quitting, but most soon reduced the frequency of stimulation. The discomfort caused by the beads was minor, and there were no significant side effects. There were technical problems with adhesiveness of the dressing. Reporting of NRT consumption was poor, with much missing data, but reporting of ratings of withdrawal symptom scores was nearly complete. However, these showed no significant changes or differences between groups for any week. Conclusion Any effects of acupressure on smoking withdrawal, as an adjunct to the use of NRT and behavioural intervention, are unlikely to be detectable by the methods used here and further preliminary studies are required before the hypothesis can be tested.